Synthesis, biological evaluation and molecular modeling of novel selective COX-2 inhibitors: sulfide, sulfoxide, and sulfone derivatives of 1, 5-diarylpyrrol-3-substituted scaffold. Issue 19 (1st October 2019) - Reale, Annalisa; Brogi, Simone; Chelini, Alessia; Paolino, Marco; Di Capua, Angela; Giuliani, Germano; Cappelli, Andrea; Giorgi, Gianluca; Chemi, Giulia; Grillo, Alessandro; Valoti, Massimo; Sautebin, Lidia; et al.
Graphical abstract: Highlights: Design, synthesis and biological evaluation of novel COX-2 selective inhibitors. COX-2 inhibitors are efficacious as analgesic agents in vivo . In silico studies highlight the binding mode of the compounds into COX-2 enzyme. Abstract: A novel series of 1, 5-diarylpyrrol-3-sulfur derivatives (10 –12 ) was synthesized and characterized by NMR and mass spectroscopy and x-ray diffraction. The biological activity of these compounds was evaluated in in vitro and in vivo tests to assess their COX-2 inhibitory activity along with anti-inflammatory and antinociceptive effect. Results showed that the bioisosteric transformation of previously reported alkoxyethyl ethers (9a-c) into the corresponding alkyl thioethers (10a-c ) still leads to selective and active compounds being the COX-2 inhibitory activity for most of them in the low nanomolar range. The oxidation products of 10a, b were also investigated and both couple of sulfoxides (11a, b ) and sulfones (12a, b ) showed an appreciable COX-2 inhibitory activity. Molecular modeling studies were performed to investigate the binding mode of the representative compounds 10b, 11b, and 12b into COX-2 enzyme and to explore the potential site of metabolism of 10a and 10b due to the different in vivo efficacy. Among the developed compounds, compound 10b showed a significant in vivo anti-inflammatory and antinociceptive activity paving the way to develop novel anti-inflammatory drugs.